Penerapan Therapy Massage Eating Difficulties Dengan Kejadian Stunting Pada Anak 0-12 Bulan - Linda Andriani; Rika Armalini; Yesi Maifita; Setia NIsa (Stikes Syedza Saintika Padang, 2025)
Stunting describes less non-nutritional status or in the period of growth and development since the beginning of life is from the nutrition of less pregnant women (kek) and in pregnancy until children are born. The incidence of stunting state is presented with a high-level Z-Score on the growth standards according to WHO. Therapy MassageIt is part of the traditional healing methods that are classified in the oldest and the most oldest and the most popular tape therapy is known to man.Eating DiffiCultiesIt can occur in all child age groups, but the type of difficulty eating and the cause is different, as well as the degree and duration. Causes of Events Difficulty May be due to a particular disease or abnormalities, but also some kind of disease or factor together. This study aims to apply the therapy massageing of tied difictiones with stunting events in children 0-12 months in the work area of the Sungai Limau of 2023. TypeThis study included quantitative research where the research design used isdesignquasi ecperimental,withOne Group Pretest and Post Test Design.This research was conducted in the Limau River Puskesmason the date of August 30- 12 September 2024. The population in this study is family with stunting children, with 11 samples. The results of the implementation of the implementation of the implementationTherapy Massage Eating DiffiStiesWith the stunning event on child 0-12 months daded p value = 0,000 & 0,001 <0,05 which means there is a relationship betweenTherapy Massage Eating DiffiStiesWith the stunning event on child 0-12 months.It is expected that the active role of the government, especially health workers to cope with the stunting events in children because children are the successor and the world of dunians. It is expected to parents to apply the massage therapeuts inhabitati child in order to trigger eating napsu in children.